Gas and Steam Permeation Properties of Cation-Exchanged ZSM-5 Membrane - Yuichiro Hirota; Masaki Nakai; Kasumi Tani; Koya Sakane; Ayumi Ikeda; Yasuhisa Hasegawa; Sadao Araki (Membranes)
NaZSM-5 powder and membranes were hydrothermally prepared. Their (1) steam (H2O) adsorption properties and (2) the permeation and separation of gas and H2O were evaluated before and after the cation exchange of Na+ to K+ or Cs+. The quantity of adsorbed H2O decreased as the size of the cation increased, indicating that the micropore volume and effective pore size of ZSM-5 decreased after cation exchange. The H2 and N2 permeances after cation exchange were less than 5% of the values before cation exchange, indicating a significant reduction in gas permeability. In contrast, the reduction of the H2O permeance values of the ZSM-5 membranes before and after K+ or Cs+ exchange was lower than that of H2, resulting in improved H2O/H2 separation performance. Compared with the NaZSM-5 membrane, the K+- or Cs+-exchanged ZSM-5 membranes exhibited superior H2O permselectivity, particularly at dilute H2O concentrations (<1 vol%).